Development of Performance Management in Refrigerated Transportation Company PT WET Logistics Indonesia Based on the Balanced Scorecard (BSC) - Widaningsih Widaningsih; Raden Dikky Indrawan; Popong Nurhayati (Pelopor Publikasi Akademika, 2026)
PT WET Logistics Indonesia is a company engaged in the refrigerated truck rental sector. To improve service quality, PT WET Logistics Indonesia has implemented integrated Industry 4.0 technology through the Transportation Management System (TMS), Global Positioning System (GPS), and data thermologger (DTL) across its fleet, positively impacting the company's revenue. Nonetheless, management realizes that developing a long-term strategy cannot rely solely on financial performance indicators and customer satisfaction. This dependence risks delays in responding to changes in the business environment and lost strategic opportunities. Therefore, this research aims to design the stages of strategy formulation by translating the company's vision, mission, and strategy into four Balanced Scorecard (BSC) perspectives and developing a strategic map based on cause-and-effect relationships. The research method involves performance management design aligned with the company's vision and strategy, supported by Focus Group Discussions (FGD) and interviews with stakeholders. The results show that the strategy formulation stage yields an elaboration of the vision, mission, and strategy into four BSC perspectives. The strategic planning stage produces a strategic map, 13 strategic goals, 15 critical success factors (CSF), and 17 key performance indicators (KPIs) with priority targets and weights determined using the Saaty scale (1–9). Furthermore, 39 strategic initiatives were formulated and are monitored through a BSC-based performance management dashboard with a traffic light control system.